PENGARUH TARIF PAJAK, TEKNOLOGI DAN INFORMASI PERPAJAKAN, TERDETEKSI KECURANGAN DAN KETEPATAN PENGALOKASIAN PAJAK TERHADAP TAX EVASION - Tirza Oktovianti Lenggono (Soso-Q : Jurnal Manajemen, 2019)
The number of taxpayers increases from year to year. However, the increase in the number of taxpayers is not offset by awareness of taxpayers in paying taxes. The problem of tax evasion is an obstacle in maximizing tax revenue. The purpose of this study is to determine the effect of tax rates, technology and information taxation, fraud detected, and accuracy of tax allocation for tax evasion.This research was conducted by convenience sampling method with a sample of 100 respondents from WPOP UMKM in 4 districts. Data obtained by distributing questionnaires. Analysis of the data used in this study are the validity and reliability tests, as well as the classical assumption test (Multicollinearity test, heteroscedasticity test, normality test) and multiple regression analysis, coefficient of determination and hypothesis testing (F statistical test and t statistical test).The results of this study indicate that tax rates have no significant effect on tax evasion, technology and tax information have a significant positive effect on tax evasion, detected fraud has a significant negative effect on tax evasion, accuracy of tax allocation does not have a significant effect on tax evasion. Keywords: Tax rates, tax technology and information, fraud detected, tax allocation accuracy, tax evasion